From Line to Stanza: Unraveling the Poetic Structure of Psalm 136 Using Insights from Roman Jakobson - Werse, Nicholas R. (Scandinavian journal of the Old Testament, 2025)
By applying Jakobson’s methodology, this article examines the poetic structure of Ps 136. Each stanza builds upon the grammatical matical patterns of the preceding stanza to expand the description of God. The God that is initially identified by titles (vv.1-3) comes to be identified by actions (vv.4-9), stories (vv.10-15, 17-22), and the literary present (vv.23-25). This structure identifies vv.16 and 26 as strategic monostich lines that emphasize the theme of YHWH’s universal kingship in the psalm.